Mismatch negativity-like potential (MMN-like) in the subthalamic nuclei in Parkinson's disease patients - Minks, Eduard; Jurák, Pavel; Chládek, Jan; Chrastina, Jan; Halámek, Josef; Shaw, Daniel J; Bareš, Martin (Journal of neural transmission, 2014)
An infrequent change to an otherwise repetitive sequence of stimuli leads to the generation of mismatch negativity (MMN), even in the absence of attention. This evoked negative response occurs in the scalp-recorded electroencephalogram (EEG) over the temporal and frontal cortices, 100-250 ms after onset of the deviant stimulus. The MMN is used to detect sensory information processing. The aim of our study was to investigate whether MMN can be recorded in the subthalamic nuclei (STN) as evidence of auditory information processing on an unconscious level within this structure. To our knowledge, MMN has never been recorded in the human STN. We recorded intracerebral EEG using a MMN paradigm in five patients with Parkinson's disease (PD) who were implanted with depth electrodes in the subthalamic nuclei (STN). We found far-field MMN when intracerebral contacts were connected to an extracranial reference electrode. In all five PD patients (and nine of ten intracerebral electrodes), we also found near-field MMN-like potentials when intracerebral contacts were referenced to one another, and in some electrodes, we observed phase reversals in these potentials. The mean time-to-peak latency of the intracerebral MMN-like potentials was 214 ± 38 ms (median 219 ms). We reveal MMN-like potentials in bilateral STN. This finding provides evidence that STN receives sensory (auditory) information from other structures. The question for further research is whether STN receives such signals through a previously described hyperdirect pathway between STN and frontal cortex (a known generator of the MMN potential) and if the STN contributes to sensorimotor integration.
Keywords: akustická stimulace; Magnetic Resonance Imaging; Evoked Potentials, Auditory; funkční lateralita; Contingent Negative Variation; Female; Parkinsonova nemoc; Neuropsychological Tests; Acoustic Stimulation; reakční čas; sluchové evokované potenciály; Functional Laterality; ženské pohlaví; neuropsychologické testy; lidé; magnetická rezonanční tomografie; Subthalamic Nucleus; stupeň závažnosti nemoci; tomografy rentgenové počítačové; Parkinson Disease; Male; Aged; nucleus subthalamicus; Reaction Time; lidé středního věku; Tomography Scanners, X-Ray Computed; senioři; mužské pohlaví; Severity of Illness Index; elektroencefalografie; Middle Aged; kontingentní negativní variace; Electroencephalography; Humans